Psychopathological Symptoms, Social Skills, and Personality Traits: A Study with Adolescents - Garaigordobil Landazábal, Maite (The Spanish Journal of Psychology, 2006)
The purpose of this study is two-fold: (a) to study the concomitant relationships between psychopathological symptoms, cooperation, social skills, and other personality traits; and (b) to identify the predictive variables of psychopathological symptoms. The sample consists of 322 adolescents aged 14 to 17 years old. This study uses correlational methodology. In order to assess psychopathological symptoms, cooperation, social skills, and personality traits, the following scales are used: the Symptom Checklist (SCL-90-R; Derogatis, 1983), the Cooperativeness Scale (CS; Rigby, Cox, & Black, 1997), the MESSY social skills scale (Matson, Rotatori, & Helsel, 1983), and the TPT Personality Test (Corral, Pamos, Pereña, & Seisdedos, 2002). Pearson coefficients suggest that adolescents with many psychopathological symptoms have low levels of cooperative behaviors and social skills. They also score high in inappropriate assertiveness, impulsiveness, overconfidence, and jealousy-withdrawal and have low levels of emotional stability, sociability, and responsibility. Through multiple regression analyses, the following variables were identified as predictors of psychopathological symptoms: jealousy-withdrawal, low social integration, impulsiveness, and low self-concept. The role played by intervention programs promoting socio-emotional development to prevent psychopathological symptoms and enhance mental health is discussed.
Keywords: Psychopathological symptoms; Social behaviors; Personality; Adolescence